Agitating Images : Photography against History in Indigenous Siberia - Campbell, Craig (Book collections on Project MUSE., 2014)
'Agitating Images' explores the early history of Communist organisation among small dispersed groups of indigenous Evenki peoples of Central Siberia. It draws this history into an examination of the destabilising role of photographs in the production of history. While documenting the development of Soviet Nationalities policy in context of people who were considered to be socially and technologically 'backwards', the project is resolutely committed to the demonstration of what the author calls photographic agitation.